1966
DOI: 10.1063/1.1708103
|View full text |Cite
|
Sign up to set email alerts
|

Damping Peaks in Deformed Nickel

Abstract: The internal-friction spectrum of zone-refined nickel [R(273°K)/R(4.2°K)=600] has been examined at 30 kc/sec, in the temperature range 77°-350 o K. Plastic deformation produces two prominent relaxation peaks, each the sum of several simple peaks. At 30 kc/sec, one peak, which occurs at 138°±7°K, has been identified as the Niblett and Wilks peak, and the other, which has its maximum at 248°±40oK, has been shown to be the Bordoni peak. Both peaks have been studied as a function of cold work, grain size, state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…However, Mecs and Nowick (1968) found that, for a silver single crystal of (1 11) orientation, the peak after a deformation of only 0.5 % was very broad and occurred at a temperature some 20 degrees higher than when the deformation was increased to 5.4 %. This agrees very closely with the behaviour we observed for copper, and even larger temperature shifts have been reported for nickel by Sommer and Beshers (1966) and Venkatesan and Beshers (1970). For each metal the peak occurs at a relatively high temperature for small prior stresses, and its temperature falls with increasing deformation ; in some cases the temperature of the peak begins to rise again for high deformations.…”
Section: Discussionsupporting
confidence: 91%
“…However, Mecs and Nowick (1968) found that, for a silver single crystal of (1 11) orientation, the peak after a deformation of only 0.5 % was very broad and occurred at a temperature some 20 degrees higher than when the deformation was increased to 5.4 %. This agrees very closely with the behaviour we observed for copper, and even larger temperature shifts have been reported for nickel by Sommer and Beshers (1966) and Venkatesan and Beshers (1970). For each metal the peak occurs at a relatively high temperature for small prior stresses, and its temperature falls with increasing deformation ; in some cases the temperature of the peak begins to rise again for high deformations.…”
Section: Discussionsupporting
confidence: 91%
“…Further deformation to 21 % caused the peak to increase in height and moved it to a slightly higher temperature. These effects are in qualitative agreement with the work of Sommer and Beshers (1966) the magnitudes of the changes in the temperature of the peak appear to be much smaller for copper.…”
Section: Polycrystalline Specimenssupporting
confidence: 87%
“…In particular, the peak is usually considerably broader than that calculated for a single relaxation process, and its temperature has been found to depend to some extent on the amount of prior deformation and on the impurity content of the specimen. Such changes in the temperature of the peak are usually only a few degrees, but Sommer and Beshers (1966) and Venkatesan and Beshers (1970) have observed considerably larger variations for nickel when the amount of cold work was changed. Seeger's original theory has been modified by Part (1961), by Seeger andSchiller (1962, 1966), by Alefeld (1967), and by Engelke (1969aEngelke ( ,b, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which the experimental results eliminate certain categories of mechanisms will also be mentioned, in preparation for the detailed discussion of mechanisms in Section 13.2. That the Bordoni peak is general to all fee metals is shown by the fact that it has been observed not only in copper and aluminum, on which the most detailed studies have been made, but also in silver, gold, palla dium, and platinum (Bordoni, et al, 1960;Okuda, 1963a,b), as well as in lead (Welber and Quimby, 1958), and nickel (Sommer and Beshers, 1966).…”
Section: Description Of the Bordoni Peak In Fee Metalsmentioning
confidence: 98%